Management Characteristics, Managerial Ownership and Innovative Efficiency in High-technology Industry. - Cosh, A; Fu, X; Hughes, A (SLPTMD (Department of International Development, University of Oxford), 2007)
This paper explores the impact of management characteristics and managerial ownership on a firm’s innovation performance in transforming innovation resources into commercially successful outputs. These questions are investigated using a recent firmlevel survey database for 440 innovative British small and medium enterprises (SMEs) over the period 1998-2001. Both Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA) are employed to benchmark each firm’s innovative efficiency against best practice. Quality and the variety of innovations are taken into account by combining Principal Component Analysis (PCA) with DEA. We find evidence suggesting that the innovative efficiency of SMEs is significantly affected by their management characteristics and ownership structure. Formality in management structure, incentive design and human resource management practices all show significant effects on the innovative efficiency of firms. Managerial ownership is found to have a nonmonotonous, non-linear relationship with the firms’ innovative efficiency, supporting both an alignment effect and an entrenchment effect of managerial ownership on the innovation performance of firms. Results of this study reveal a significant moderating influence of the industry’s technological environment on the relationship between management characteristics, ownership structure and innovative efficiency of firms. Evidence from this study suggests that formal management structure and training intensity play a more important role in commercialising innovation inputs in hightechnology sectors; while incentive schemes and managerial ownership are more important for innovative efficiency in the traditional sectors.